2012
DOI: 10.1038/psp.2012.20
|View full text |Cite
|
Sign up to set email alerts
|

Simulations to Assess Phase II Noninferiority Trials of Different Doses of Capecitabine in Combination With Docetaxel for Metastatic Breast Cancer

Abstract: A phase II trial in metastatic breast cancer (MBC) (NO16853) failed to show noninferiority (progression-free survival, PFS) of capecitabine 825 mg/m2 plus docetaxel 75 mg/m2 to the registered capecitabine dose of 1,250 mg/m2 plus docetaxel 75 mg/m2. We developed a modeling framework based on NO16853 and the pivotal phase III MBC study, SO14999, to characterize the link between capecitabine dose, tumor growth, PFS, and survival to simulate response to a range of capecitabine doses and determine a minimum capeci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 17 publications
2
25
0
Order By: Relevance
“…However, any estimate of untreated TG is complicated by the lack of information on TG and death in the absence of treatment because all patients received ECX, and the estimate of TG is based on data from patients who are resistant or develop resistance to treatment. The gastric/GEJ tumor doubling time is slightly higher than the time for colorectal tumors, 8 to 12 months (31), but lower than the 40 months needed in breast tumors (32). These findings clearly reflect the differences in disease progression due to the primary tumor origin.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…However, any estimate of untreated TG is complicated by the lack of information on TG and death in the absence of treatment because all patients received ECX, and the estimate of TG is based on data from patients who are resistant or develop resistance to treatment. The gastric/GEJ tumor doubling time is slightly higher than the time for colorectal tumors, 8 to 12 months (31), but lower than the 40 months needed in breast tumors (32). These findings clearly reflect the differences in disease progression due to the primary tumor origin.…”
Section: Discussionsupporting
confidence: 48%
“…The effect of ECX in killing tumor cells indicated that the time to reduce tumor size by half from baseline was approximately 2 months, and it took 1.5 months on average to develop resistance to ECX treatment. The dynamic for the resistance phenomena has been previously determined for other anticancer drugs (32). Thus, in breast cancer, the half-lives of the resistance phenomenon for capecitabine and docetaxel were determined to be 3.25 and 4 months, respectively (32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bruno et al . described SLD data from metastatic breast cancer patients treated with a combination of docetaxel and capecitabine using the TGI model assuming an additive effect of both drugs and resistance development for both drugs.…”
Section: Population Modelling Of Tumour Sizementioning
confidence: 99%